Biotransformation of Dairy Waste into ACE-Inhibitory Peptides: A Sustainable Strategy for Blood Pressure Management: Biotransformation of Dairy Waste into ACE-Inhibitory Peptides - Yasmeen, Roheela; Sattar, Amna; Aslam, Aneeza; Ali, Hamna (Futuristic Biotechnology, 2026)
The bioactive peptides produced by valorization of dairy by-products, specifically whey and casein wastes, are a sustainable approach to the treatment of environmental pollution as well as the health requirements of the population. This review is dedicated to the biotransformation of dairy waste through enzymatic hydrolysis and fermentation with the help of such strains as Lactobacillus helveticus, Lactobacillus brevis, and Pediococcus acidilactici to produce angiotensin-converting enzyme (ACE)-inhibitory peptides, including Val-Pro-Pro and Ile-Pro-Pro. These peptides show good antihypertensive, antioxidant, and anti-inflammatory effects both in vitro and in animals. Independent bioprocessing methods, such as enzyme immobilization and nanoencapsulation, have been used to improve the yield, stability, and bioavailability of peptides. Nevertheless, there are major shortcomings such as inconsistent effects of peptides in clinical trials, lack of human clinical trials, and the inability to scale production, yet keep costs economical. The issue of regulation is also an obstacle to translation because the approval of health claims needs to be based on strong clinical evidence and stable quality, which is not the case at present. This model focuses on waste utilization and sustainability; hence, minimizing the environmental load of dairy effluent and value addition of agro-industrial waste streams. To maximize the potential of dairy waste-based ACE-inhibitory peptides, the main agendas in the future are to put human trials first, standardize production protocols, and provide regulatory directions to attain safety, efficacy, and economic sustainability.